The Effectiveness of Prenatal Yoga on Improving Sleep Quality of Pregnant Women in The Third Trimester: A Quasi Experimental Study at Bah Kapul and Simarimbun Health Centres, Pematangsiantar City - Parmiana Bangun; Yeyen Damanik (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Disturbances in sleep are common among pregnant women, especially in the third trimester, and can negatively impact the health of both the mother and fetus. Non-pharmacological approaches, such as prenatal yoga, offer a safe and effective way to improve sleep quality. This study aims to evaluate the effectiveness of prenatal yoga in enhancing sleep quality, blood pressure, and breathing among pregnant women in the third trimester in the Bah Kapul and Simarimbun Health Centre areas, Pematangsiantar City. A quasi-experimental design was employed, with an intervention group (n = 30) and a control group (n = 30). The intervention group participated in prenatal yoga sessions lasting 60 minutes, three times a week, for eight weeks (minimum 12 sessions). Sleep quality and disturbance were measured using a dedicated assessment tool, and data analysis was conducted with SPSS. Results showed that prior to the intervention, most participants in both groups reported poor sleep quality. After the intervention, significant improvements were observed in the intervention group (p < 0.001), including a reduction in severe sleep disturbances from 6.7% to 0%. The median sleep quality score increased by 1 point in the intervention group, compared to no change in the control group (p = 0.010), while the sleep disturbance score decreased by a median of 4 points in the intervention group (p = 0.019). No significant changes were found in blood pressure or breathing (p > 0.05). The study received ethical approval from the Health Research Ethics Committee of Politeknik Kesehatan Kemenkes Medan (Reference No: 01.26.696 /KEPK/POLTEKKES KEMENKES MEDAN 2024), and written informed consent was obtained from all participants. In conclusion, prenatal yoga significantly improved sleep quality and reduced sleep disturbances in pregnant women in the third trimester and is recommended as part of the antenatal care program at health centers. Keyword: Prenatal Yoga, Pregnant Women, Sleep Disorders, Sleep Quality, Third Trimester.